FABRICATION OF GERMANIUM-DOPED SILICA OPTICAL FIBRES USING MCVD TECHNIQUES TO ENHANCE DOSIMETRIC CHARACTERISTICS FOR GAMMA-RAY DETECTION IN BLOOD IRRADIATOR - Noor, Noramaliza Mohd Noor; Ku Bakar, Ku Shaidaton Akmar; .Bradley, David Andrew; Dolah, Mohd Taufik (Asian Journal Of Medical Technology, 2025)
This study explores the fabrication of germanium-doped silica optical fibers using Modified Chemical Vapor Deposition (MCVD) techniques to enhance dosimetric properties for gamma-ray detection in blood irradiators. Accurate dose mapping, essential for preventing graft-versus-host disease, requires radiation exposure in the range of 15 Gy to 50 Gy. We investigate the dosimetric characteristics of Ge-doped silica fibers as passive radiation dosimeters for blood irradiators using a Cs-137 source. Key dosimetric parameters, including linearity, sensitivity, fading, and glow curve analysis, were tested on cylindrical (CF) and flat (FF) fibers, irradiated with doses from 5 to 50 Gy. Thermoluminescence (TL) measurements showed a linear dose response (R² > 99%) and consistent sensitivity, with Coefficients of Variation improving from 12.8% to 5.57% for CF and 13.8% to 5.91% for FF. After 28 days of storage, TL fading was 11.5% for CF and 9.2% for FF. The MCVD technique, along with germanium doping, significantly improved the dosimetric properties of the fibers, making both CF and FF Ge-doped optical fibers promising candidates for passive dosimetry in gamma-ray blood irradiators.